Indeks Pencemaran Lingkungan Secara Fisika-Kimia dan Biokonsentrasi Timbal (Pb) pada Kerang Hijau di Perairan Pesisir Semarang Utara - Khusnia, Arsika Zuhrotul; Astorina, Nikke; Rahardjo, Mursid (Universitas Diponegoro, 2019)
The North Semarang ocean are functioned for high activity area also utilization in one site. The entry of waste into the waters or oceans caused the decrease of water quality.Â Lead (Pb) entered to North Semarang oceans by kind of activities there. The aims of this researc are to describe pollution index and bioconcentration in the study location. This reasearch is descriptive observational with cross sectional study. Sampling location determined beside on zoonation.Twenty four (24) samples were determined purposively besed on location, wind direction and current type. The samples was measured in situ and laboratory test. The average of pH was 8,05 , temperature wasÂ 31,38Â°C, salinity was 28,4 ppt, DO was 4,07 mg/L and lead (Pb) was 0,99 mg/L. The average of dissolved oxygen not in accordance with quality standards (>5 mg/l) also lead (Pb) average is higher than standard (0,008 mg/l). Calculation of pollutan index in North Semarang ocean categorized as moderate polluted and the lead (Pb) bioconcentration on Perna viridis categorized as low accumulative with the value of BCF was 0,62 L/kg (BCF<100). All of samples classified as moderate polluted which caused bioconcentration and low bioacumulation on Perna viridis so that it is harmful for human health.